2013
DOI: 10.1007/s12975-012-0247-9
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the Rho/Rho-Kinase Pathway and Prevention of Cerebral Vasospasm by Combination Treatment with Statin and Fasudil After Subarachnoid Hemorrhage in Rabbit

Abstract: The Rho/Rho-kinase pathway is considered important in the pathogenesis of sustained smooth muscle cell contraction during cerebral vasospasm after aneurysmal subarachnoid hemorrhage (SAH). The aims of this study were to investigate whether combination treatment, with pitavastatin as an inhibitor of RhoA and fasudil as an inhibitor of Rho-kinase, prevents the cerebral vasospasm. SAH was simulated using the double-hemorrhage rabbit model, and pitavastatin, or fasudil, or both (combination treatment) were adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 41 publications
3
25
0
1
Order By: Relevance
“…The Rho/Rho-kinase pathway is the main regulator of these actin-dependent cell functions in the pathogenesis of sustained smooth muscle cell contraction and vasospasm (Satoh et al, 2012; Takai et al, 1995). Therefore, the combination of treatment with an inhibitor of RhoA, pitavastatin, and an inhibitor of Rho-kinase, fasudil, could extensively prevent cerebral vasospasm after SAH (Naraoka et al, 2013). Furthermore, phosphorylations trigger SAH-induced vasculopathy in cerebral arteries, as determined by quantitative mass spectrometry, including focal adhesion complexes, ERK1/2, calcium calmodulin-dependent kinase II, STAT3, and c-Jun (Parker et al, 2013).…”
Section: 3 Neurobiological Response After Sahmentioning
confidence: 99%
“…The Rho/Rho-kinase pathway is the main regulator of these actin-dependent cell functions in the pathogenesis of sustained smooth muscle cell contraction and vasospasm (Satoh et al, 2012; Takai et al, 1995). Therefore, the combination of treatment with an inhibitor of RhoA, pitavastatin, and an inhibitor of Rho-kinase, fasudil, could extensively prevent cerebral vasospasm after SAH (Naraoka et al, 2013). Furthermore, phosphorylations trigger SAH-induced vasculopathy in cerebral arteries, as determined by quantitative mass spectrometry, including focal adhesion complexes, ERK1/2, calcium calmodulin-dependent kinase II, STAT3, and c-Jun (Parker et al, 2013).…”
Section: 3 Neurobiological Response After Sahmentioning
confidence: 99%
“…It was suggested that hydroxyfasudil was contributed to the potency of fasudil to prevent CVS and hyperviscosity, and the potential utility of hydroxyfasudil as a therapeutic agent for patients with SAH was also suggested. However, Naraoka M et al [28] employed the double-hemorrhage rabbit model to investigate whether the combination treatment, consisting of pitavastatin as an inhibitor of RhoA and fasudil as an inhibitor of Rho-kinase, prevented CVS. And the results showed the cross-sectional area of basilar artery were significantly increased only by the combination treatment, and the separate use of fasudil or pitavastatin had no significant effect.…”
Section: Fasudilmentioning
confidence: 99%
“…The cholesterollowering drugs known as statins inhibit 3-hydroxy-3methylglutaryl-coenzyme A, thereby inhibiting the synthesis of isoprenoids (geranyl-geranyl pyrophosphate) and cholesterol, leading to inhibition of Rho-kinase and increased NO production [11]. Combined treatment with the Rho-kinase inhibitor fasudil and statins prevents cerebral spasm after subarachnoid hemorrhage [12]. However, exposure to cold temperatures causes vessels to constrict via a mechanism involving reactive oxygen speciesinduced activation of Rho-kinase, alpha-2 adrenoceptor translocation and decreased NO production [13].…”
Section: Introductionmentioning
confidence: 99%